Infrared thermography applied to the surface pressure measurements in insoluble surfactant monolayers. Issue 1 (1st January 2023) - Vinnichenko, Nikolay; Pushtaev, Alexey; Plaksina, Yulia; Uvarov, Alexander
ABSTRACT: New experimental technique, based on IR thermography, is proposed to measure the surface pressure for dilute monomolecular films of surfactants on a liquid surface. The surfactant molecules are distributed unevenly along the surface, which leads to the formation of surface regions of two kinds. Part of the surface is covered with surfactant film, which suppresses the surface renewal and inhibits the heat transfer between the surface and the bulk liquid. Thus, these regions possess lower temperature compared to the rest of the surface, free of surfactant and exhibiting both buoyant and thermocapillary convection. High sensitivity of the modern IR cameras allows the measurement of the temperature difference between the surface regions, from which the surface pressure can be derived. Experiments with myristic acid are performed for different values of the surface temperature and mean concentration of the surfactant. The results demonstrate that it is possible to measure the surface pressure for liquid-expanded films with area per molecule up to 500 \char 197 2 . The derived parameters of 2D van der Waals gas are in agreement with published data . The proposed technique can also be used to compare the contamination level in dilute films of insoluble and soluble surfactants.